1988
DOI: 10.1016/s0022-5347(17)41803-9
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Prostatitis Following Bacillus Calmette-Guerin Immunotherapy of Bladder Cancer

Abstract: Granulomatous prostatitis is a recognized complication of intravesical bacillus Calmette-Guerin immunotherapy of superficial bladder cancer. Of 32 patients receiving such therapy 13 underwent prostatic core biopsy and/or fine needle aspiration for clinical indications. Prostatic induration or nodularity developed in 12 patients and 1 underwent biopsy for staging of known prostatic carcinoma. Granulomatous prostatitis was found in 100 per cent of those patients who underwent biopsy or aspiration, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…Orchitis and granulomatous prostatitis have been observed by many other authors [see reference 1], but have not been observed in this series of patients. Oates et al have shown that in patients with prostatitis following BCG immuno therapy, granulomatous lesions were found in all 13 patients who underwent prostatic biopsy aspiration [3]. In 3 of these patients, acid-fast bacilli were demonstrated within the prostate.…”
Section: Loco-regional Disseminationmentioning
confidence: 99%
“…Orchitis and granulomatous prostatitis have been observed by many other authors [see reference 1], but have not been observed in this series of patients. Oates et al have shown that in patients with prostatitis following BCG immuno therapy, granulomatous lesions were found in all 13 patients who underwent prostatic biopsy aspiration [3]. In 3 of these patients, acid-fast bacilli were demonstrated within the prostate.…”
Section: Loco-regional Disseminationmentioning
confidence: 99%
“…In our case, diagnosis was made by histopathological examination of the prostate biopsy specimens harvested because of suspect prostate cancer after detection of increased PSA levels, and abnormal DRE findings. Oates et al [8] performed prostate biopsies in 13 patients who received intravesical BCG therapy in 1988, and all pathology reports indicated presence of granulomatous prostatitis. In a study conducted by La Fontaine et alin 1997, granulomatous prostatitis was detected in 75% of 119 patients who had initially received intravesical BCG therapy, then undergone radical cystoprostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a higher incidence of granulomatous prostatitis was found in patients who had been treated with intravesical bacille CalmetteGuerin. [1][2][3][4] Extrapulmonary tuberculosis has been increasing in patients with AIDS, although prostatic tuberculosis is still rare. 5 6 Tuberculosis may be spread from the kidney through the urinary tract, haematogenous spread, direct extension form adjacent foci, and lymphatic spread.…”
Section: Discussionmentioning
confidence: 99%